ESTUDIO DEL EFECTO DE DIFERENTES MEDIOS SOBRE ALEACIONES DE ALUMINIO RECICLADO PARA USO DOMÉSTICO - Pizarro C., R. (2009)
This research aims to study and conduct assessment of !he speed up of corrosion of aluminum alloys used far domestic as well as !he influence of corrosive agents present to make use of these domestic articles in means of different pHs. To study three means were chosen: Acid mean (solution of Acetic ac id pH = 4.8), Basic mean (solution of sodium hydroxide pH = 9 .5) and Saline mean (solution of sodium chloride pH = 7.8) and tour types of aluminum alloys far use common: FAM or 1100 alloy as standardized pattern sample, R-1, R-2 and R-3 as samples of recycled aluminum. The tests showed that FAM is the most resistant material to the three aggressive means and it is the material with a lower content of impurities , R-3 is !he most attacked and is the material with the highest percentage of impurities. The most aggressive mean corresponds to the Saline mean and it is precisely !he most used mean.